The effect of a coordination training program on the development of tennis service technique - Tsetseli, M.; Malliou, V.; Zetou, E.; Michalopoulou, M.; Kambas, A. (Biology of Exercise, 2010)
The aims of the present study were: i) to define which coordination abilities are the most important in tennis and ii) to evaluate whether a coordination training program will improve the service technique. The study was conducted on 48 children (age 11 ± 2 years). The participants were randomly divided into a control group (C) and an intervention group (A) that performed a specific coordination program 3 imes/wk. Both groups (C and A) followed a tennis training program 3times/wk. The service technique was evaluated in all subjects in the beginning of the protocol (T0), after the completion of the 5-week specific coordination program (T5) and one week after the intervention program was completed (T6). The present study, suggests that the most important coordination abilities for tennis players are kinaesthetic differentiation and reaction time. Furthermore, two-way repeated measurements ANOVA revealed that there was significant increase (p 0.05) on the service technique between groups (C and A) and among the different phases (T0, T5 and T6).